Energetics and thermoregulation during digging in the rodent tuco-tuco (Ctenomys talarum) - Luna, Facundo (2007)
For subterranean rodents, searching for food by extension of the tunnel system and maintenance of body temperature are two of the most important factors affecting their life underground. In this study we assess the effect of ambient temperature on energetics and thermoregulation during digging in Ctenomys talarum. We measured V o(2) during digging and resting at ambient temperature (T(a)) below, within, and above thermoneutrality. Digging metabolic rate was lowest at T(a) within the thermoneutral zone and increased at both lower and higher temperatures, but body temperature (T(b)) remained constant at all T(a)s. Below thermoneutrality, the cost of digging and thermoregulation are additive. Heat production for thermoregulation would be compensated by heat produced as a by-product of muscular activity during digging. Above thermoneutrality, conduction would be an important mechanism to maintain a constant T(b) during digging.